PRESENCE OF Triatoma tibiamaculata (PINTO) NYMPHS IN PERIDOMICILES, IN SALVADOR, BAHIA - Santana, Karine de Souza Oliveira; Bavia, Maria Emília; Ribeiro-Jr, Gilmar José da Silva; Santos, Carlos Gustavo Silva dos; Guimarães, Isabel Cristina Santos; Silva, Marta Mariana Nascimento; Dias-Lima, Artur Gomes (Revista de Patologia Tropical / Journal of Tropical Pathology, 2014)
Chagas disease is associated with the domiciliation of infected vectors migrating from their natural ecotopes. The appearance of nymphs in the peridomicile, in Salvador, Bahia, confirms the need for epidemiological surveillance. The vectors were captured from 2006 to 2009, by the population and by epidemiological field agents with the Chagas Disease Control Program. Three hundred and sixty two nymphs of the species Triatoma tibiamaculata (Pinto, 1926) were captured in the peridomicile and 13.5% of these nymphs were infected with Trypanosoma cruzi (Chagas, 1909). Nymphs were near the houses, a possible risk for colonization. Surveillance of the peridomicile is an important element to prevent colonization by disease vectors.